B- i could be wrong though
<span>Here let the quadratic equation be ax^2 + bx + c
We know that a=5 from the question.
Since the roots are 6 and 2, the quadratic equation would take the form of a product like (a1x-b1)(a2x-b2).
However, let's assume that a2=1 and b2=6,
Since a=5, a1=5, then 5x-b1=5(x-2). Solving this shows that b1=10
So, the equation is (5x-10)(x-6)</span>
70, 7*10 since it is 1/10 of that number
Answer:
No
Step-by-step explanation:
When you square a number, you chose a number and multiplying itself. If you did the square root of 25, you would get 5. However if you divided 25 by 2, you would get 12.5 which is NOT the square root.